Factors Related to Compliance of Mothers Consuming Kb Pills in Dameria Midwife Clinic Sembiring Karang Rejo Stabat Year 2021 - Deby Cintya Yun (Science Midwifery, 2022)
The increase in population is one of the global problems that arise throughout the world, in addition to global warming, economic downturn, food problems and the declining level of population health. This study aims to determine the factors of maternal adherence to taking birth control pills at the Dameria Br Sembiring Karang Rejo Midwife Clinic in 2021. This type of research is an analytical survey research using a cross sectional design, which is a type of research that emphasizes measurement time or data observation of independent and dependent variables only once. at a certain point in time by measuring or simultaneously observing the risk/exposure factors with effects. The results of the study with the number of respondents as many as 32 people regarding the factors related to maternal adherence to taking birth control pills. The age factor, knowledge and husband's support are related to maternal compliance with taking birth control pills at the Dameria Midwife Clinic Br Sembiring Karang Rejo Stabat in 2021 with a p-value of 0.000 (p-value 0.05), the age factor of work and maternal compliance with taking birth control pills at the Dameria Midwife Clinic Br Sembiring Karang Rejo Stabat in 2021 with a p-value of 0.002 (p-value 0.05), the husband's support factor is a strong factor related to maternal compliance with taking birth control pills at the Dameria Midwife Clinic Br Sembiring Karang Rejo Stabat in 2021. From several factors, namely the husband's support factor, it is strong factors related to maternal adherence to taking birth control pills at the Dameria Clinic Br Sembiring Karang Rejo Stabat in 2021 with a logistic regression p-value It is hoped that the results of this study can be used as additional data for further researchers, especially factors related to adherence.